Detection of Gastrointestinal Pathogens from Stool Samples on Hemoccult Cards by Multiplex PCR. (16th March 2017) - Alberer, Martin; Schlenker, Nicklas; Bauer, Malkin; Helfrich, Kerstin; Mengele, Carolin; Löscher, Thomas; Nothdurft, Hans Dieter; Bretzel, Gisela; Beissner, Marcus
Abstract : Purpose . Up to 30% of international travelers are affected by travelers' diarrhea (TD). Reliable data on the etiology of TD is lacking. Sufficient laboratory capacity at travel destinations is often unavailable and transporting conventional stool samples to the home country is inconvenient. We evaluated the use of Hemoccult cards for stool sampling combined with a multiplex PCR for the detection of model viral, bacterial, and protozoal TD pathogens. Methods . Following the creation of serial dilutions for each model pathogen, last positive dilution steps (LPDs) and thereof calculated last positive sample concentrations (LPCs) were compared between conventional stool samples and card samples. Furthermore, card samples were tested after a prolonged time interval simulating storage during a travel duration of up to 6 weeks. Results . The LPDs/LPCs were comparable to testing of conventional stool samples. After storage on Hemoccult cards, the recovery rate was 97.6% for C. jejuni, 100% for E . histolytica, 97.6% for norovirus GI, and 100% for GII. Detection of expected pathogens was possible at weekly intervals up to 42 days. Conclusion . Stool samples on Hemoccult cards stored at room temperature can be used in combination with a multiplex PCR as a reliable tool for testing of TD pathogens.